Sixth-Graders Learn from Letter Writing - Crowhurst, Marion ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This study was conducted to determine some of the effects of dyadic writing interactions on the writing of sixth graders, and specifically, to describe the effects of corresponding with pen pals who were students in a language arts methods course during their professional teacher education year. Twenty-seven sixth-grade students attended a school in a lower middle-class area close to the campus of the university where the teacher education students were enrolled. Each sixth grade student was paired with a teacher education student. Letters were exchanged weekly from September until December. The effect of writing to a real audience was gauged by comparing the first letters with later letters. Changes of the following kinds were most noticeable: length, syntactic complexity, paragraphing, and various communicative features (such as: openings and closings, questions, taking up topics, and expressions of appreciation). The education students found the correspondence personally rewarding and learned important things about the writing of sixth graders including an appropriate balance between formal matters and content. For the sixth-graders, the experience was rewarding both personally and as a learning experience as was evident in comments they made in their letter and in journal entries to their teacher. Both the students and their teacher considered writing to their pen pals a highly motivating activity. The sixth-graders were eager to adopt strategies that would help them communicate more clearly and effectively. (Seventeen references are attached.) (MG)
Sponsoring Agency: British Columbia Univ., Vancouver.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audience Awareness; Audience Response; College School Cooperation; Grade 6.; Higher Education; Intermediate Grades; Letters (Correspondence); Student Attitudes; Student Writing Models; Writing Improvement; Writing Processes; Writing Research; Writing Skills; Pen Pals -- Writing Development; Childrens Writing -- Purpose (Composition) -- Writing Contexts; Reports, Research